# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }+y^{\prime }-6 y = 6
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+{y^{\prime }}^{2}+4 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = -4 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-3 x y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+2 x \right ) y^{\prime \prime }-2 \left (1+x \right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}-2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-\omega ^{2} x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+42 x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 \gamma x^{\prime }+\omega _{0} x = F \cos \left (\omega t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-2 y = {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 2 \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = 16 \cos \left (4 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = \cosh \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x \left (1+x \right )^{2} y^{\prime \prime }+\left (-x^{2}+1\right ) y^{\prime }+\left (x -1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}x \left (1-x \right ) y^{\prime \prime }+2 \left (1-2 x \right ) y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+\frac {y^{\prime }}{2}+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime \prime }-y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}x \left (x -1\right )^{2} y^{\prime \prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+\left (1-x \right ) y^{\prime }+m y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-2 y = 8
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = 10 \,{\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = {\mathrm e}^{-2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+25 y = 5 x^{2}+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 4 \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+5 y = 2 \,{\mathrm e}^{-2 x}
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime }-2 y^{\prime }-y = 2 x -3
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+8 y = 8 \,{\mathrm e}^{4 x}
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }-7 y^{\prime }-4 y = {\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+9 y = 54 x +18
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+6 y = 100 \sin \left (4 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 4 \sinh \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-2 y = 2 \cosh \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }+10 y = 20-{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+4 y = 2 \cos \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+3 y = x +{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+3 y = x^{2}-1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y = {\mathrm e}^{3 x}+\sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+3 x = {\mathrm e}^{-3 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+5 y = 6 \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-3 x^{\prime }+2 x = \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = 3 \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+10 y = 50 x
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+2 x^{\prime }+2 x = 85 \sin \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 3 \sin \left (x \right )-4 y
\] |
✓ |
✓ |
|
\[
{}\frac {x^{\prime \prime }}{2} = -48 x
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+5 x^{\prime }+6 x = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-2 y = 4 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-2 y = {\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-2 y = \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+25 y = 2 \sin \left (\frac {t}{2}\right )-\cos \left (\frac {t}{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+25 y = 64 \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+25 y = 50 t^{3}-36 t^{2}-63 t +18
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 9 x^{2}+2 x -1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y = 2 \,{\mathrm e}^{5 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = x^{2}-1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 4 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 4 \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 3 \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{x}}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-2 y = {\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x = \sin \left (2 t \right )^{2}
\] |
✓ |
✓ |
|
\[
{}t^{2} N^{\prime \prime }-2 t N^{\prime }+2 N = t \ln \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{x}}{x^{5}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sec \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-2 y = {\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-60 y^{\prime }-900 y = 5 \,{\mathrm e}^{10 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-7 y^{\prime } = -3
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {y^{\prime }}{x}-\frac {y}{x^{2}} = \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-x y^{\prime } = {\mathrm e}^{x} x^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-3 y = \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = 3 \,{\mathrm e}^{-2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+5 y^{\prime }-3 y = \operatorname {Heaviside}\left (x -4\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}q^{\prime \prime }+9 q^{\prime }+14 q = \frac {\sin \left (t \right )}{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 4-x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }+2 y = 2 \left (1-x \right ) {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }+2 y = {\mathrm e}^{5 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = x \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-y^{\prime }+4 x^{3} y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+{y^{\prime }}^{2}+1 = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+{y^{\prime }}^{2} = 2
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime }+{y^{\prime }}^{3} = 0
\] |
✓ |
✓ |
|